Rhabdomyolysis after group C streptococcal infection - Hilde Haugedal Nordal; Bård Reiakvam Kittang; Laurence Albert Bindoff (MDPI AG, 2010)
We describe a young woman with a group C streptococcal throat infection complicated by rhabdomyolysis. Muscle biopsy from quadriceps was normal, and molecular studies showed no evidence of direct microbial invasion. This is only the second case in which the usually benign group C streptococcus has been linked with muscle destruction.